Organic Farmer Field School (FFS) and the Implementation of Quality Control Systems in Sustainable Farming Practices - Mutiarra Ridyo Arum; Suswadi; Dewi Rahmawati Intan Permatasari; A. Peni (Journal of Community Capacity Empowerment, 2026)
The market prospects and price stability of Javanese long pepper (Piper retrofractum Vahl) indicate that this commodity has the potential to generate profit and bolster the economy as a leading commodity in Wonogiri Regency, particularly in Paranggupito District. To capitalize on these opportunities, the produced yields must adhere to specific standards, notably organic certification. This community service initiative aimed to enhance farmers' technical proficiency in the production and implementation of organic fertilizers, as well as to improve their capacity in implementing quality control systems. The program was conducted in Gudangharjo Village, Paranggupito District, Wonogiri Regency, utilizing the Farmer Field School (FFS) methodology. The outcomes of this activity include: (1) An increase in farmers' knowledge regarding Javanese long pepper cultivation through the application of both solid and liquid organic fertilizer technologies. (2) The establishment of demonstration plots (demplots) to facilitate direct participation in organic cultivation practices aligned with organic Good Agricultural Practices (GAP). (3) The successful formulation of organic GAP Standard Operating Procedures (SOPs) by farmers, serving as a formal guideline for cultivation to ensure uniform and high-quality organic Javanese long pepper production.